2019
DOI: 10.1111/tra.12648
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress and oxygen availability drive differential changes in opossum kidney proximal tubule cell metabolism and endocytosis

Abstract: Kidney proximal tubule (PT) cells have high-metabolic demands to drive the extraordinary ion and solute transport, water reabsorption, and endocytic uptake that occur in this nephron segment. Increases in renal blood flow alter glomerular filtration rate and lead to rapid mechanosensitive adaptations in PT transport, impacting metabolic demand. Although the PT reabsorbs essentially all of the filtered glucose, PT cells rely primarily on oxidative metabolism rather than glycolysis to meet their energy demands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 55 publications
(75 reference statements)
3
25
0
Order By: Relevance
“…Subsequent studies demonstrated that growing OK cells under continuous shear stress and with increased O 2 availability dramatically improved their baseline endocytic capacity by roughly 5-fold compared with cells maintained under static conditions (Long et al 2017). In addition to increased expression of megalin and cubilin, cells cultured in this manner acquire morphological, transport, metabolic and transcriptional adaptations characteristic of PTs in vivo, including dense microvilli, greater sodium transport capacity, and oxidative metabolism (Long et al 2017;Ren et al 2019;Park et al 2020). Similar to the observations using cells cultured under static conditions and exposed acutely to flow, endocytic capacity in this more differentiated cell model is rapidly and reversibly regulated by changes in FSS (Long et al 2017).…”
Section: Endocytic Adaptation To Variations In Gfrsupporting
confidence: 62%
“…Subsequent studies demonstrated that growing OK cells under continuous shear stress and with increased O 2 availability dramatically improved their baseline endocytic capacity by roughly 5-fold compared with cells maintained under static conditions (Long et al 2017). In addition to increased expression of megalin and cubilin, cells cultured in this manner acquire morphological, transport, metabolic and transcriptional adaptations characteristic of PTs in vivo, including dense microvilli, greater sodium transport capacity, and oxidative metabolism (Long et al 2017;Ren et al 2019;Park et al 2020). Similar to the observations using cells cultured under static conditions and exposed acutely to flow, endocytic capacity in this more differentiated cell model is rapidly and reversibly regulated by changes in FSS (Long et al 2017).…”
Section: Endocytic Adaptation To Variations In Gfrsupporting
confidence: 62%
“…We recently developed an opossum kidney (OK) cell model cultured under continuous shear stress that recapitulates key features of PT function, including well-differentiated apical and basolateral plasma membrane domains, increased energy utilization and ion transport, and dramatically expanded apical endocytic capacity (27). Similarly to the PT in vivo, these cells rely on oxidative metabolism for energy production, thus enabling us to better address the specific role of fatty acid ligands carried by albumin in overload responses (34). Using this model, we asked how exposure to nephrotic concentrations of human serum (HuSer), to FAF-BSA, or to BSA complexed with different ligands affects cellular outcomes known to be associated with proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…To establish a link between SARS-CoV-2-related genes to drugs, we used a commercial drug database of Metacore version 20.3 build 70200 from Clarivate Analytics [15] and IPA [14]. To highlight the most promising drugs that might be repurposed for COVID-19 treatment, only drug targets that were either FDA approved or had been examined in clinical trials were selected.…”
Section: Methodsmentioning
confidence: 99%
“…To establish a link between SARS-CoV-2-related genes to drugs, we used a commercial drug database of Metacore version 20.3 build 70200 from Clarivate Analytics [15] and IPA [14].…”
Section: Mapping Sars-cov-2-related Degs To Fda Approved/ Clinical Drugsmentioning
confidence: 99%